Guided Discovery Learning and Cognitive Style: Keys to Success in Primary Geometry Education - Sholeh, Abdul; Tjalla, Awaluddin; ., Yurniwati (Journal of Ecohumanism, 2025)
This study aims to explore how the Guided Discovery Learning model and cognitive style affect geometry learning outcomes among primary school students in Cirebon City. An experimental research design with a 2 x 2 factorial structure was applied for this study. Probability sampling, specifically area cluster sampling, was used to select 167 participants. Data collection involved administering tests and questionnaires. The analysis of the data included both descriptive and inferential statistics, with prerequisite tests for normality using the Shapiro-Wilk test and homogeneity using Levene's test. Statistical significance was assessed using a two-way ANOVA, followed by post hoc Scheffé tests at a significance level of ά = 0.05. The findings revealed that: (1) students taught with the Guided Discovery Learning model had better geometry learning outcomes than those taught with the Problem-Based Learning model, (2) there was an interaction between learning models and cognitive style on geometry learning outcomes, (3) students with a field-independent cognitive style performed better when taught through the Guided Discovery Learning model compared to those using the Problem-Based Learning model, and (4) students with a field-dependent cognitive style also achieved higher geometry learning outcomes when taught using the Guided Discovery Learning model rather than the Problem-Based Learning model. Therefore, both learning models and cognitive styles significantly impact geometry learning outcomes.